Mio-Pliocene Faunal Exchanges and African Biogeography: The Record of Fossil Bovids - Bibi, Faysal (Public Library of Science, 2011)
The development of the Ethiopian biogeographic realm since the late Miocene is here explored with the presentation and review of fossil evidence from eastern Africa. Prostrepsiceros cf. vinayaki and an unknown species of possible caprin affinity are described from the hominid-bearing Asa Koma and Kuseralee Members (∼5.7 and ∼5.2 Ma) of the Middle Awash, Ethiopia. The Middle Awash Prostrepsiceros cf. vinayaki constitutes the first record of this taxon from Africa, previously known from the Siwaliks and Arabia. The possible caprin joins a number of isolated records of caprin or caprin-like taxa recorded, but poorly understood, from the late Neogene of Africa. The identification of these two taxa from the Middle Awash prompts an overdue review of fossil bovids from the sub-Saharan African record that demonstrate Eurasian affinities, including the reduncin Kobus porrecticornis, and species of Tragoportax. The fossil bovid record provides evidence for greater biological continuity between Africa and Eurasia in the late Miocene and earliest Pliocene than is found later in time. In contrast, the early Pliocene (after 5 Ma) saw the loss of any significant proportions of Eurasian-related taxa, and the continental dominance of African-endemic taxa and lineages, a pattern that continues today.